AKT inhibition impairs PCNA ubiquitylation and triggers synthetic lethality in homologous recombination-deficient cells submitted to replication stress - Villafañez, Florencia (2019)
Translesion DNA synthesis (TLS) and homologous recombination (HR) cooperate during S-phase to safeguard replication forks integrity. Thus, the inhibition of TLS becomes a promising point of therapeutic intervention in HR-deficient cancers, where TLS impairment might trigger synthetic lethality (SL). The main limitation to test this hypothesis is the current lack of selective pharmacological inhibitors of TLS. Herein, we developed a miniaturized screening assay to identify inhibitors of PCNA ubiquitylation, a key post-translational modification required for efficient TLS activation. After screening a library of 627 kinase inhibitors, we found that targeting the pro-survival kinase AKT leads to strong impairment of PCNA ubiquitylation. Mechanistically, we found that AKT-mediated modulation of Proliferating Cell Nuclear Antigen (PCNA) ubiquitylation after UV requires the upstream activity of DNA PKcs, without affecting PCNA ubiquitylation levels in unperturbed cells. Moreover, we confirmed that persistent AKT inhibition blocks the recruitment of TLS polymerases to sites of DNA damage and impairs DNA replication forks processivity after UV irradiation, leading to increased DNA replication stress and cell death. Remarkably, when we compared the differential survival of HR-proficient vs HR-deficient cells, we found that the combination of UV irradiation and AKT inhibition leads to robust SL induction in HR-deficient cells. We link this phenotype to AKT ability to inhibit PCNA ubiquitylation, since the targeted knockdown of PCNA E3-ligase (RAD18) and a non-ubiquitylable (PCNA K164R) knock-in model recapitulate the observed SL induction. Collectively, this work identifies AKT as a novel regulator of PCNA ubiquitylation and provides the proof-of-concept of inhibiting TLS as a therapeutic approach to selectively kill HR-deficient cells submitted to replication stress.